KEWENANGAN PEMERINTAH DAERAH PROVINSI DKI JAKARTA DALAM PENGENAAN TARIF PROGRESIF PAJAK KENDARAAN BERMOTOR TAHUN 2021-2022: The Authority Of The Dki Jakarta Province Regional Government Is Based On Law Number 1 Of 2022 In Imposition Of Progressive Rates Of Vehicle Tax Motorcycling In 2021-2022 - Vonna Della Monika; Januardo Sihombing (Faculty of Law, Universitas Trisakti, 2025)
This research is motivated by the authority of Regional Governments to set progressive Motor Vehicle Tax rates as regulated in Law Number 1 of 2022 concerning Financial Relations between Central and Regional Governments. The identification of the problem in this study is the authority of the Jakarta Provincial Government to set progressive rates on motor vehicle ownership during the 2021–2022 period based on the provisions of the law. The type of research used is normative legal research with a descriptive-analytical approach. Data collection was conducted through literature study of secondary legal materials. Data analysis was carried out qualitatively with conclusions drawn using deductive methods. Based on the research results and conclusions, it is concluded that until now the Jakarta Provincial Government still uses the provisions in Jakarta Provincial Regulation Number 2 of 2015 concerning Amendments to Provincial Regulation Number 8 of 2010 on Motor Vehicle Tax in applying progressive rates. However, with the effective implementation of Law Number 1 of 2022 in January 2024, the Jakarta Provincial Government will prepare a new Regional Regulation to replace all previous regulations in accordance with Article 94 of the law that mandates the unification of regional regulations for all types of regional taxes.